2008
DOI: 10.1021/jp801559t
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Specific Vacuum Ultraviolet Mass-Analyzed Threshold Ionization Spectroscopy of Alkanethiols: Structure and Ionization of Conformational Isomers of Ethanethiol, Isopropanethiol, 1-Propanethiol, tert-Butanethiol, and 1-Butanethiol

Abstract: Conformational isomers of alkanethiols are isolated in the molecular beam, and the conformer-specific ionization dynamics have been investigated using vacuum ultraviolet mass-analyzed threshold ionization (MATI) spectroscopy. Only a single conformer of ethanethiol is observed to give the adiabatic ionization potential (IP) of 9.2922 +/- 0.0007 eV for the gauche conformer. For isopropanethiol, IP is found to be 9.1426 +/- 0.0006 for the trans conformer and 9.1559 +/- 0.0006 eV for the gauche conformer. Only two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Experimental measurements reported T–G as the global minimum (although one earlier experiment based on IR absorption identified T–T as the global minimum) with one local minimum conformer G–T or T–T conformers, respectively. 2–8 The scan with initial geometry as the optimized G–G conformer resulted in T–G as the global minimum conformer and G–G as the local minimum which is similar to the prediction by Gorai et al 1 and Choi et al 9 Furthermore, the results reported herein match exceedingly well with the experimental results. Table ST2† summarizes all conformational scans for the nP molecule at the CCSD/cc-pVDZ level of theory with a step size of 5°.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Experimental measurements reported T–G as the global minimum (although one earlier experiment based on IR absorption identified T–T as the global minimum) with one local minimum conformer G–T or T–T conformers, respectively. 2–8 The scan with initial geometry as the optimized G–G conformer resulted in T–G as the global minimum conformer and G–G as the local minimum which is similar to the prediction by Gorai et al 1 and Choi et al 9 Furthermore, the results reported herein match exceedingly well with the experimental results. Table ST2† summarizes all conformational scans for the nP molecule at the CCSD/cc-pVDZ level of theory with a step size of 5°.…”
Section: Resultssupporting
confidence: 89%
“…The results reported herein correlate exceedingly well with the available experimental results for the propylthiol molecular system. 1–3,6,7,9,10 Computations of normal modes and electrostatic potential charge (ESP), Mulliken charge analysis (MCA), natural bond orbital analysis (NBO), frontier molecular orbital (FMO), and non-covalent interaction (NCI) were also carried out to support further the results pertaining to the conformational stability of nP and 2P molecules. It is envisaged that with the results reported herein, the unambiguity pertaining to the conformational aspects of nP would cease, and these results may serve as a benchmark for conformational analysis of the propylthiol molecular system.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational constants, torsional barriers (V 3 = 1329 cm −1 ), and dipole moments were derived by Schmidt and Quade 21 using microwave spectroscopy. Theoretical papers on ETSH have also been published 22,23 using relatively low levels of theory and small basis sets.…”
Section: Introductionmentioning
confidence: 99%
“…The ionization energy (IE) of ethanethiol is 9.2922 ± 0.0007 eV. 37 Photoionization with 118.2 nm (10.487 eV) VUV light produced the parent ion, C 2 H 6 S + , at m/z 62 and a 34 S 1 isotopomer peak at m/z 64. The (64/62) isotope is calculated to be 4% for C 2 H 6 S + , which is consistent with natural abundance.…”
Section: Results: Thermal Decomposition Of Ethanethiolmentioning
confidence: 99%